(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. Compared to the conventional methods, serum beta-trace protein (BTP) has been shown to be more helpful for estimating glomerular filtration rate; however, its value is remained unclear in neonates. The present study aimed to investigate the range of serum BTP level in healthy term neonates and its value to estimate glomerular filtration rate. Materials and Methods. This cross-sectional study was conducted on 50 healthy term neonates without underlying cardiovascular or kidney disorders who were admitted to Ali Asghar hospital in 2013. Serum BTP was measured using an automated nephelometric immunoassay. Glomerular filtration rate was assessed using the Schwartz equation based on serum creatinine level. Results. The mean age of the neonates was 6.2 ± 3.6 days (range, 2 to 17 days), their mean gestational age was 38.02 ± 0.20 weeks, and their mean height was 49.8 ± 1.7 cm. The mean serum BTP level was 0.41 ± 0.11 mg/L (range, 0.19 mg/L to 0.92 mg/L). The mean serum creatinine level was 0.49 ± 0.16 mg/dL (range, 0.3 mg/dL to 1.0 mg/dL). The mean estimated GFR was 48.90 ± 15.88 mL/min. A positive correlation was observed between the reciprocal concentrations of BTP and GFR (r = 0.383, P = .006). Furthermore, the reciprocal concentrations of BTP was associated with the reciprocal concentrations of serum creatinine level (r = 0.365, P = .009). Conclusions. Measurement of serum BTP can be a reliable tool for detecting kidney function in neonates. Further studies are warranted to design a suitable formula for GFR estimation based on serum BTP in neonates.